Genetic Variants of Bank1 Gene in Autoimmune Thyroid Diseases: A Case-Control Association Study - Muhali, F.-S.; Song, R.-H.; Wang, X.; Shi, X.-H.; Jiang, W.-J.; Xiao, L.; Li, D.-F.; He, S.-T.; Xu, J.; Zhang, J.-A. (Experimental and Clinical Endocrinology & Diabetes, 2013)
To investigate BANK1 gene variation, and its association with autoimmune thyroid disease and clinical features.We genotyped 3 single nucleotide polymorphisms (SNPs) rs10516487, rs3733197 and rs4522865 of BANK1 gene in 667 patients with autoimmune thyroid diseases (417 with Graves’ disease and 250 with Hashimoto’s thyroiditis) and 301 healthy controls. The Matrix Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometer (MALDI-TOF-MS) Platform was used to detect the 3 SNPs.There was a significant association in rs3733197 A allele and AITD patients (P=0.043). SNP rs3733197 A allele was found in 29.63% chromosome of AITD patients who are 18 years old or below, compared with 19.90% chromosome in those 19 years or above (P=0.017). Also SNP rs3733197 A allele showed a significant association in HT patients when compared with controls (P=0.031, OR=0.73 and 95% CI=0.55–0.97). Stratification for specific autoantibodies in AITD patients TGAb positive when compared with SE (shared epitope) positive showed a significant association in rs3733197 SNP (P=0.010, OR=0.68 and 95%=CI 0.51–0.91). However, no significant association was found between 3 SNPs and GD.Our findings suggest the existence of association between BANK1 gene and AITD thus adding BANK1 gene to the list of the predisposing genes to AITD.
Keywords: BANK1; single nucleotide polymorphisms (SNPs); autoimmune thyroid disease; Graves’ disease; Hashimoto’s thyroiditis